A New Blood Corpuscle - Gaetano, Giovanni de (Thrombosis and Haemostasis, 2001)
At the occasion of the first centennial anniversary of Giulio Bizzozero’s death (1901), an impossible interview is presented to honour this distinguished and creative investigator. The imaginary conversation between a reporter and Bizzozero – aged 36 years – takes place at the University of Turin in 1882, few months after Bizzozero’s announcement of the discovery of a new blood corpuscle with seemingly important function in thrombosis and blood coagulation. “An investigator who is not prepared in advance to look for other than the known elements – says Bizzozero – will be attracted only by the red and white corpuscles.”Having discovered blood platelets, Bizzozero, convinced that scientific and social progress should proceed hand in hand, will turn – as a scientist and a member of the Italian Kingdom’s Senate – to such social issues as the welfare of the poor.He will die in Turin, aged 55 years, shortly after Giuseppe Verdi, few months before the conferment of the first Nobel Prize for Medicine (to E. von Behring).
Keywords: Blood platelets; blood coagulation; leukocytes; thrombosis; history of medicine